Evaluation of Seepage Force and Overall Stability Factor Along Proposed Baghdad Metro Tunnel Across Tigris River (Journal of Engineering, 2023)
Baghdad Metro is a vital project to fulfill the rapidly increased traffic volume requirements. The proposed metro will connect both sides of Baghdad City, passing under the Tigris River. This study is employed finite elements software (PLAXIS 3D) to evaluate the seepage force developed around the sub-river segment during different construction stages and for other water levels of Tigris. The study found that when the water level changes from maximum to minimum, the developed seepage force decreases by (8 to 13%) and (22 to 27%) respectively. The seepage forces were found to be maximum during the excavation stage. The concrete lining process led to a noticeable reduction in seepage forces at all locations. The study also implemented the strength reduction theory to assess the overall stability of the tunnel. The study shows that the overall stability factor was minimum during the concrete lining process. As the water level decreased, the overall stability factor increased by (5% - 8%).